SEXUAL HEALTH AND VIOLENCE, A SUBJECT WORTH ASKING ABOUT? ADAPTATION OF SEXUAL HEALTH IDENTIFICATION TOOL FOR ADULTS (SEXIT-A) - Solenzal, A Gainza; Elmerstig, E; Bjerså, K; Weineland, S; Hammarström, S (Journal of sexual medicine, 2025)
Objectives: Few patients voluntarily disclose problems with sexual health, experiences of violence, and risk-taking behaviors to their health care providers. Despite health care providers being aware of the importance of these topics, few regularly address these areas in outpatient settings. This is often due to a lack of knowledge about sexual health among providers and a fear of embarrassing patients by asking questions that might be perceived as private or intrusive.To address these challenges, the SEXual health Identification Tool (SEXIT) was developed. Initially designed to identify sexual ill health, experiences of violence, and risk-taking behaviors among youth through a structured questionnaire and follow-up conversation, SEXIT has proven effective in these demographics. However, there is an absence of comparable methods tailored for adult populations. Methods: This study aimed to identify the specific questions that health care providers should ask concerning sexual health, experiences of violence, and risk-taking behaviors in adult outpatient settings. Utilizing a modified Delphi methodology, a panel of 19 experts from clinical and academic fields was recruited. Results: In the end, 25 questions were identified as highly relevant. These questions cover topics including sexual and gender identity, sexual satisfaction, experiences of violence, and substance use.The findings from this study provide a deeper understanding of the pertinent questions that should be integrated into medical history taking to address sexual health, experiences of violence, and risk-taking behaviors. By incorporating these questions, health care providers can bridge the knowledge gaps commonly experienced in the Sexual and Reproductive Health and Rights (SRHR) field. Moreover, this approach can remove the barriers that patients face when attempting to discuss these sensitive issues. Conclusions: The questions identified have been included in the development of the first version of the SEXIT Adult questionnaire. This tool, along with the accompanying guidance for health care providers, is currently undergoing clinical evaluation. The implementation of SEXIT Adult holds promise for enhancing the identification and management of sexual health issues, experiences of violence, and risk-taking behaviors in adult outpatient settings, ultimately contributing to improved patient well-being. Conflicts of Interest: There are no potential conflicts of interests.